Introduction to economic growth - Jones, Charles I.; Vollrath, Dietrich (New York W.W. norton and company, 2024)
Introduction to Economic Growth, Fourth Edition is the only text to synthesize the research and thinking on growth in a way that is accessible to undergraduates. Highlights of this thorough revision are its emphasis and discussion of recent advancements in how we understand our economy of ideas and updates to show how core models$1 (BRomer, Solow, and Schumpeter$1 (Bimpact decision making.s
Keywords: Economic development; Economic indicators; Economic growth